Socio-demographic characteristics of female criminals at the Kajang women prison, Malaysia / Rachel Samuel, Roaimah Omar and Rohana Ariffin - Samuel, Rachel; Omar, Roaimah; Ariffin, Rohana (Research Management Institute (RMI), 2012)
The criminal behavior of women has been studied less than that of men. This could be because women commit fewer crimes than men, especially violent offences, and also because female crime would typically be carried out in private and domestic spheres. In addition, women's roles as mothers, society's taboo towards female violence and consequent denial have possibly reduced the concern of this issue. In Malaysia, out of 39, 258 prisoners in 2008, only 9% were females (Malaysian Stats, 2009). Historically, women have been more likely to commit minor offenses and have made up only a small proportion of the offender population. It is generally accepted that women commit a small share of all crimes, which are less serious and less professional in nature, resulting in their smaller representation within the criminal justice system (Heidensohn, 1994). This suggests that gender may be of greater statistical significance in differentiating between criminals and noncriminals than any other characteristic (Worrall. 2001). However, globally, there is a rising trend.in the percentage of female offenders and their participation in violent crime. The increase is related to personality characteristics, substance misuse and prior criminal behavior of the offenders (Putkonen, Komulainen, Virkkunen, Eronen & Lonnqvist, 2003). Though the numbers of the offenders seem insignificant, this research was carried out to have an in-depth understanding of who the female offenders in Malaysia are and what types of crimes are they incarcerated for. More than half of the female prison population in Malaysia is made up of foreigners from poorer neighboring countries with immigration offenses being the highest in terms of committed crimes. The focus of this research however was only the Malaysian female offenders, which makes up a much smaller percentage than the 9% stated above.